Modernity and typology: Some questions about the architecture of Le Corbusier (ARQUISUR Revista, 2017)
This work came up from a postgraduate seminar at FADU–UNL, that discussed if the composition of Le Corbusier ́s regulatory tracings or the recurrence of prototypical solutions to serial housing constituted typological manipulations, with the question appearing of how these operations were articulated with the projecting logic of modernity. This idea triggered an inquiry that was later deepen trough a seminar given by the author in this school since 2004 on the pertinence of framing Le Corbusier as a «typologist». The goal of this work was centered on verifying the possibilities and richness that the concept of «type» can present to analyze Le Corbusier work, showing explicit or implicit allusions to the concept made by the historiography or the critic, and inquiring on the theoretical production of Le Corbusier for the approach to this concept.
Keywords: modern architecture; typology; model; Le Corbusier